INVESTIGATION INTO EFFECTIVENESS OF NATIONAL DIRECTORATE OF EMPLOYMENT (NDE) TRAINING STRATEGY ON CLUSTER OF BUSINESS LINKAGES AND DOMESTIC INVESTMENT TOWARDS POVERTY REDUCTION (NAU Journal of Technology and Vocational Education, 2024)
The paper examined the effectiveness of National Directorate of Employment (NDE) trainingstrategy on cluster of business linkages and domestic investment towards povertyreduction. Two research questions guided the study. The population consisted of 47,298beneficiaries of NDE training in Oyo State, total of 4,729 respondents were selectedthrough stratified sampling technique. The study adopted survey design. A four pointstructured questionnaire was used for data collection. The instrument was validated byfour experts. An internal consistency of 0.80 was obtained using Croncbach Alphacorrelation co-efficient. Mean and standard deviation were used to answer the researchquestions. The study showed that the cluster of business linkages and domesticinvestment training strategies of NDE were effective. It was concluded that NDE trainingstrategies reduced unemployment problems in Oyo State. It was recommended amongothers that linkages, networking, collaboration and association should take priority in theNDE training and that the NDE should continue its training ondomestic investment.
Keywords: Effectiveness, Cluster, Business Linkages, Domestic Investment.